Antibacterial Activity of Gentamicin Sulfate in Tissue Culture - Rudin, A. (1970)
Gentamicin is a more effective in vitro bacterial inhibitor than combined penicillinstreptomycin, is nontoxic to tissue culture monolayers, and does not inhibit virus replication.